Determinants of awareness and practice of breast self examination among rural women in Trichy, Tamil Nadu - Hemalatha Kumarasamy; A M Veerakumar; S Subhathra; Y Suga; R Murugaraj (Wolters Kluwer Medknow Publications, 2017)
Introduction: Breast cancer is the most common cancer among women worldwide, and it can be detected at an early stage through self-examination which increases the chance of survival. This study aimed to assess knowledge and practice of breast self-examination (BSE) among females in a rural area of Trichy district. Methodology: This community-based, cross-sectional study was carried out among a total sample of 200 women in rural area of Trichy. The participants were interviewed using a structured interviewer-administered questionnaire to obtain information on their sociodemographic characteristics, awareness on breast cancer, and knowledge, attitude, practice of BSE. Data were entered into MS Excel and analyzed using SPSS version 20.0. Spearman correlation and Chi-square test were used to analyze the association between the variables. Results: The mean age of the study group was 36.9 ± 8.8 years. Eighty percent were literates. Most of the women 178 (89%) were aware of breast cancer. Only 26% of the women were aware of BSE. Only 18% of the females had ever checked their breast and 5% practiced it regularly. Awareness of BSE was found to be significantly associated with age and educational attainment. Conclusion: The level of knowledge and practice of BSE among females are unacceptably low. Efforts should be made to increase level of knowledge and practice of BSE through health education programs.